Strategies to Enhance Citizen Participation through Innovation in Environmental Education Programs Based on Multi-Stakeholder Collaboration and Digital Technology - Azzaakiyyah, Hizbul Khootimah; Suherlan; Suparwata, Dewa Oka (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2025)
This study aims to analyze strategies for enhancing citizen participation in environmental education through program innovations based on multi-stakeholder collaboration and the use of digital technology. The method employed is a literature review with a qualitative approach and descriptive analysis, primarily intended to enrich references related to community service in the field of environmental studies. Data were collected from scholarly articles in Google Scholar and credible websites within the period of 1977–2025. From the initial 50 articles identified, 27 were selected through a strict screening process based on relevance, quality, and contribution to the research topic. The findings reveal that enhancing citizen participation is influenced by cross-sector collaboration, innovative learning design, and the application of interactive and inclusive digital technologies. Theories such as Civic Engagement, Collaborative Governance, the Technology Acceptance Model, Self-Determination Theory, Social Learning, and Diffusion of Innovations provide relevant conceptual foundations for understanding the dynamics of participation. Case studies such as the Climate Village Program (ProKlim), Digital Waste Bank in Bandung, and Pentingsari Tourism Village in Yogyakarta provide empirical evidence of the successful implementation of these strategies. This research makes an important contribution to the development of participatory-based environmental education, strengthens multi-stakeholder collaboration, and enriches sustainable community service practices.